Children's automatic evaluation of self‐generated actions is different from adults. Issue 3 (2nd November 2020) - Denervaud, Solange; Hess, Adrien; Sander, David; Pourtois, Gilles
Abstract: Performance monitoring (PM) is central to learning and decision making. It allows individuals to swiftly detect deviations between actions and intentions, such as response errors, and adapt behavior accordingly. Previous research showed that in adult participants, error monitoring is associated with two distinct and robust behavioral effects. First, a systematic slowing down of reaction time speed is typically observed following error commission, which is known as post‐error slowing (PES). Second, response errors have been reported to be automatically evaluated as negative events in adults. However, it remains unclear whether (1) children process response errors as adults do (PES), (2) they also evaluate them as negative events, and (3) their responses vary according to the pedagogy experienced. To address these questions, we adapted a simple decision‐making task previously validated in adults to measure PES as well as the affective processing of response errors. We recruited 8‐ to 12‐year‐old children enrolled in traditional ( N  = 56) or Montessori ( N  = 45) schools, and compared them to adults ( N  = 46) on the exact same task. Results showed that children processed correct actions as positive events, and that adults processed errors as negative events. By contrast, PES was similarly observed in all groups. Moreover, the former effect was observed in traditional schoolchildren, but not in Montessori schoolchildren. These findings suggest that unlike PES, which likely reflects an age‐invariant attention orienting toward response errors, their affective processing depends on both age and pedagogy. Abstract : Children process correct actions as positive events, and adults process errors as negative events. Moreover, the former effect was observed in traditionally‐schooled children, but not in Montessori‐schooled children. These findings suggest that response errors' affective processing depends on both age and pedagogy experienced at school.